(untitled) (Cardiovascular Journal, 2015)
Background: Bronchodilators, by dilatation of bronchial tree through relaxation of bronchial smooth muscle increases the vital capacity, tidal volume and total lung capacity and reduces gas trapping. This study was conducted to assess the pulmonary function after off-pump coronary artery bypass graft (CABG) surgery between patients with impaired pulmonary function treated with or without preoperative bronchodilator. We also compared duration of mechanical ventilation and days spent in the surgical intensive care unit (ICU) after CABG in both group of patients. Methods: This prospective cohort study was carried out in the department of Cardiac Surgery, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh, from July 2009 to April 2011. This study included 50 patients (25 patients in each group) with multi-vessels coronary artery disease with impaired pulmonary function who underwent off-pump CABG. Results: Spirometry was done in both groups of patients after admission, day before operation and on 7th post-operative day. The difference in Forced vital capacity (FVC) and Forced expiratory volume in 1st second (FEV1 ) between two groups were not statistically significant after admission (P>0.05). On the day before surgery the values of FVC and FEV1 were increased (more in Group-I who were treated with bronchodilator) and 7th postoperative day the values were decreased (more in Group-II who were not treated with bronchodilator). The results were found statistically significant in between groups (P<0.05). Conclusion: Bronchodilator should be considered pre-operatively in all patients having impaired pulmonary function undergoing off-pump CABG for better preservation of postoperative pulmonary function. DOI: http://dx.doi.org/10.3329/cardio.v7i2.22260 Cardiovasc. j. 2015; 7(2): 123-127